DETERMINANTS OF LOAN LOSS PROVISION USING BANK-SPECIFIC VARIABLES AND MACRO ECONOMIC FACTORS: CASE STUDY ON 19 COMMERCIAL BANKS IN INDONESIA PERIOD 2008-2017 - Fauziyah, Dini; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract.Bank in distributing loans is inseparable from the risk of impairment and uncollectible, therefore banks must anticipate these risks by preparing funds, known as Loan Loss Provision (LLP). The increase or decrease of LLP during the period of 2008 to 2017 can indicate a problem that can affect the sustainability of the banking industry and even further the country. Therefore, this research was conducted with the aim to figure out the variables that influence the increase and decrease in Loan Loss Provision. The data collected are the financial report of 19 banks which categorized in the BACB 3 and BACB 4 that obtained from the Financial Services Authority (OJK) and macroeconomic data obtained from Bank Indonesia during the first quarter of 2008 to the fourth quarter of 2017. The EGLS Panel (cross-section weight) is used to analyse the data. Regression results for six independent variables showed that two of those variables are not significant to Loan Loss Provision, namely Loan Ratio to Deposit and Growth of Gross Domestic Product. Non-Performing Loan, Capital Adequacy Ratio have a significant positive impact on Loan Loss Provision, while Bank Size and Inflation have a significant negative impact on Loan Loss Provision.Keywords: BACB, Bank, CKPN, Loan Loss Provisions, Panel Data Regression.